2018
DOI: 10.1007/s10853-018-2650-4
|View full text |Cite
|
Sign up to set email alerts
|

Response of Ti microstructure in mechanical and laser forming processes

Abstract: Microstructural deformation mechanisms present during three different forming processes in commercially pure Ti were analysed. Room temperature mechanical forming, laser beam forming and a combination of these two processes were applied to thick metal plates in order to achieve the same final shape. An electron backscatter diffraction technique was used to study the plate microstructure before and after applying the forming processes. Substantial differences among the main deformation mechanisms were clearly d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 31 publications
2
6
0
Order By: Relevance
“…These IFP maps show grain directions parallel to the plate surface normal in a central part of the laser track (top) and under the LHAZ area (bottom). The microstructural changes within the LHAZ (starting from the top towards the bottom) are evident and similar to that reported by [8] showing that these changes can be slip, grain fragmentation, recovery, grain boundary motion due to twinning, alpha-to-beta transformation, grain growth, phase transformation and recrystallization. The LHAZ in Figure 8 shows a fine-grained acicular alpha structure on the top of the LHAZ followed by columnar grains elongated in the direction perpendicular to the surface.…”
Section: Resultssupporting
confidence: 85%
See 4 more Smart Citations
“…These IFP maps show grain directions parallel to the plate surface normal in a central part of the laser track (top) and under the LHAZ area (bottom). The microstructural changes within the LHAZ (starting from the top towards the bottom) are evident and similar to that reported by [8] showing that these changes can be slip, grain fragmentation, recovery, grain boundary motion due to twinning, alpha-to-beta transformation, grain growth, phase transformation and recrystallization. The LHAZ in Figure 8 shows a fine-grained acicular alpha structure on the top of the LHAZ followed by columnar grains elongated in the direction perpendicular to the surface.…”
Section: Resultssupporting
confidence: 85%
“…Although the experimental data was used to calibrate the FEM and the FEM was used to determine the dependence of the maximum temperature on the depth of the sample for different laser power and scanning speeds, it should be noted that the FEA was used as primary purpose of serving as supporting tool in order to understand the underlying physical phenomena of the laser process and not as an exact measure for validating the results obtained with the laser scanning speed. Similar results for the sample depth have been reported by [8] in which only an approximate equation for heat transfer in titanium has been used. Therefore it can be concluded that the size of the LHAZ observed by EBSD is identical to the volume undergoing phase transformation.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations